STUDENTS` SELF-DIRECTED LEARNING IN THE PROCESS OF DEBATING - Ročāne, Maija; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Nowadays methods promoting self-directed learning have become essential as thinking processes, deep understanding and an independent desire to explore and research the learning content gain importance. One of these methods is debating, which provides students the opportunity not only to be aware of topical problems in science and society, but also to understand the significance of them in their personal lives. The analysis of the survey show that for students with experience in debating, goal achievement is greatly influenced by individual interest and motivation, while for students without debating experience teacher's positive attitude is more important than personal interest and motivation to learn.